Functional double dissociation between two inferior temporal cortical areas: perirhinal cortex versus middle temporal gyrus. - Buckley, M; Gaffan, D; Murray, E (1997)
There is both anatomic and cytoarchitectural evidence for dorsal-ventral subdivisions of the inferior temporal cortex. Despite this, there has been only limited evidence of corresponding functional subdivisions and no evidence that two adjacent cortical areas within the inferior temporal cortex, namely area TE and the perirhinal cortex, have distinctly different roles in vision and memory. We assessed the color discrimination abilities of cynomolgus monkeys with either bilateral ablation of the perirhinal cortex or bilateral ablation of the middle temporal gyrus. The stimuli were isoluminant colored squares presented on a touch screen. In each trial the subject had to learn to discriminate and select the correct choice (green) from among a maximum of eight other foils, each varying in either hue or saturation. Relative to unoperated controls, monkeys with middle temporal gyrus lesions were severely impaired in the color discrimination task, whereas monkeys with perirhinal lesions were unimpaired on this task. We also assessed the visual recognition abilities, as measured by a basic delayed nonmatching-to-sample task with trial-unique objects presented in a Wisconsin General Test Apparatus, of rhesus monkeys with bilateral middle temporal gyrus lesions. We then tested the monkeys' postoperative performance on a delayed nonmatching-to-sample task with delays and extended list lengths. The results from this experiment were compared with those from two other groups of rhesus monkeys, an unoperated control group and a group with bilateral perirhinal cortex lesions, both of which had performed the identical tasks in a previous experiment. Relative to unoperated controls, monkeys with perirhinal cortex lesions were severely impaired both in relearning the basic delayed nonmatching-to-sample task and on the postoperative performance test. In contrast, monkeys with middle temporal gyrus lesions were only mildly affected in relearning the basic nonmatching task and were unimpaired on the postoperative performance test. Thus our data demonstrate a clear functional double dissociation between the perirhinal cortex and the middle temporal gyrus. This result gives strong support to the hypothesis that the perirhinal cortex and the adjacent area TE have distinctly different roles in visual learning and memory.